CATNETS final activity report - Werner Streitberger; Torsten Eymann (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2007)
This paper presents the final activity report of the CATNETS project. It summarizes the project objectives, the contractors involved, the work performed and the final results. A description of the dissemination activities concludes the report.
urn:nbn:de:bvb:703-opus-3756
Keywords: 330; Grid Computing